2014
DOI: 10.1016/j.peh.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Coach perceptions of performance enhancement in adolescence: The sport drug control model for adolescent athletes

Abstract: Aim: We qualitatively explored the Sport Drug Control Model (SDCM; Donovan, Egger, Kapernick, & Mendoza, 2002), in order to examine coaches' perceptions of adolescent athletes' attitudes and susceptibility towards doping.Methods: Eleven coaches (M = 10) from four countries, who worked in seven different sports (athletics, basketball, kayaking, racquetball, rowing, rugby league, and rugby union) were recruited to take part in semi-structured interviews. Transcribed interviews were analyzed via a three-stage ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(69 citation statements)
references
References 42 publications
(83 reference statements)
0
67
1
Order By: Relevance
“…In regards to mental health, there is a two-to-four fold increased risk of suicide among athletes that have previously taken PEDs (Lindqvist et al, 2014). Despite PEDs representing a serious health threat, it appears that many athletes are unaware of the dangers that banned substances pose to their health (Nicholls et al, 2015). Understanding why athletes dope, and being able to better identify those who are more susceptible to doping, will enable governing bodies to expose at risk athletes to more intensive anti-doping education and long-term monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…In regards to mental health, there is a two-to-four fold increased risk of suicide among athletes that have previously taken PEDs (Lindqvist et al, 2014). Despite PEDs representing a serious health threat, it appears that many athletes are unaware of the dangers that banned substances pose to their health (Nicholls et al, 2015). Understanding why athletes dope, and being able to better identify those who are more susceptible to doping, will enable governing bodies to expose at risk athletes to more intensive anti-doping education and long-term monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Moral identity is a source of motivation to behave morally. In the context of sport, it was found that athletes who have low morale tend to be more positive about cheating (Gucciardi, Jalleh, & Donovan, 2011;Jalleh, Donovan, & Jobling, 2014;Nicholls et al, 2015). Some recent studies confirmed that moral identity negatively correlated with doping likelihood (Ring, Kavussanu, & Hurst, 2018).…”
Section: The Concept Of Cheating In Sportmentioning
confidence: 99%
“…As sport is an achievement context, it requires some competency. According to Achievement Goal Theory (Nicholls, 1989), the pursuit of achievement is related to the display of competence and to personal perceptions of success. There are two major ways that success is defined and competence is evaluated, and these are embedded within two achievement goals: task orientation and ego orientation.…”
Section: Achievement Orientation As a Negative And A Positive Predictmentioning
confidence: 99%
See 2 more Smart Citations